The Polar Express [videorecording (DVD)] - Zemeckis, Robert, 1952-; Hanks, Tom; Zemeckis, Leslie Harter; Deezen, Eddie, 1958-; Gaye, Nona; Scolari, Peter, 1954-; Van Allsburg, Chris (Warner Home Video, 2005)
When a doubting young boy takes an extraordinary train ride to the North Pole, he embarks on a journey of self-discovery that shows him that the wonder of life never fades for those who believe.